Physical activity level and food intake among BS Community Nutrition students during the COVID-19 pandemic - Hechanova, Andrea A.; Mag-usara, Regienald Armand Q.; Samson, Ysabel Alessandra O. (College of Home Economics, University of the Philippines Diliman, 2023)
The COVID-19 pandemic has caused an overall decrease in physical activity levels and an increase in excessive food intake habits leading to a declined health and well-being of university students. Thus, this study aimed to determine the relationship between physical activity levels and food intake, particularly, whether increased physical activity levels and healthier food intake are positively associated with each other among BS Community Nutrition (BSCN) undergraduate students during the pandemic. A cross-sectional correlational research design was used to determine the association, and there was a total of 22 participants from second to fourth year BSCN from the University of the Philippines – Diliman. The International Physical Activity Questionnaire - Short Form (IPAQ-SF) and four-day estimated food record forms were used to determine the physical activity levels and assess the food intake, respectively. The data was analyzed using descriptive statistics and Cramer’s V coefficient. It was found that there were 18.18% inactive, 50% minimally active, and 31.82% health-enhancing physical activity participants. Furthermore, 63.64% of participants had adequate energy intake while 36.36% had inadequate energy intake. Based on the quantitative analysis, this study concludes that physical activity has a large effect size (V = 0.3997) on the total energy intake. Hence, targeting physical activity may be a strategic way to improve an individual’s total energy intake. Other variables related to food intake such as macronutrients and micronutrients may be included to determine each nutrient’s relationship to physical activity. Future research may also study on university students with different programs of study.